Testing the applicability of the twin deficits hypothesis in Zimbabwe - Mandishekwa, Robson; Tambudzai, Zachary; Marufu, Alex (IISTE, 2016)
The concept of the twin deficit hypothesis is fraught with controversy. Some economists argue that there is independence between current account deficits and budget deficit while some believe that the relationship exists but the direction of causality is uncertain. While others say there is causality running from budget deficit to current account deficit and vice versa. The majority of economists trained in the Keynesian thinking are in favour of the twin deficits hypothesis while others are against it but in favour of the contrasting theory, the Ricardian equivalence. The Ricardian equivalence hypothesis, argues that the two are independent. The major objective of the paper is to test the applicability of the twin deficits hypothesis to Zimbabwe. This is premised on the argument of persistent budget and current account deficits obtaining in Zimbabwe. The majority of researches done along this line are not in Southern Africa. A Granger representation alongside co-integration analysis is used in the study. The findings indicate that the twin deficit hypothesis holds using Johansen cointegration and Granger causality based on lag two. The public expenditure overruns should be a thing of the past.